2018
DOI: 10.1111/iar.12261
|View full text |Cite
|
Sign up to set email alerts
|

Progressive changes in lithological association of the Sanbagawa metamorphic complex, Southwest Japan: Relict clinopyroxene and detrital zircon perspectives

Abstract: The main tectono‐stratigraphic unit (Shirataki unit) of the Sanbagawa metamorphic complex in central Shikoku is characterized by abundant mafic schist layers that show the mid‐ocean ridge basalt (MORB) affinity. These MORB‐derived schist layers are absent in a southern (structurally lower) domain within the unit. Instead, sporadic occurrences of small metabasite lenses that contain relict igneous minerals (Ti‐rich augite and kaersutite) indicative of alkali basalt magmatism are newly recognized in the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 63 publications
6
30
0
Order By: Relevance
“…The relationships between ages and lithostratigraphic position imply that the depositional ages of the trench‐fill sediments of the Minawa unit young gradually towards the lower structural levels of the Minawa unit (Figure ). The oldest depositional age (for sample IK‐17 from just below the upper subunit of the Minawa unit) is similar to the youngest clusters of zircon U–Pb ages (87 ±2 and 94 ±1Ma) obtained for the upper parts of the Iyo units in western Shikoku (Knittel et al, ), and also similar to the ages (90.3 ±2.2 and 90.4 ±3.0 Ma) obtained for the upper part of the Shirataki unit in central Shikoku (Endo et al, ). These similarities suggest that the depositional ages of trench‐fill sediments in close contact with the main mafic schist of the Minawa unit are c .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The relationships between ages and lithostratigraphic position imply that the depositional ages of the trench‐fill sediments of the Minawa unit young gradually towards the lower structural levels of the Minawa unit (Figure ). The oldest depositional age (for sample IK‐17 from just below the upper subunit of the Minawa unit) is similar to the youngest clusters of zircon U–Pb ages (87 ±2 and 94 ±1Ma) obtained for the upper parts of the Iyo units in western Shikoku (Knittel et al, ), and also similar to the ages (90.3 ±2.2 and 90.4 ±3.0 Ma) obtained for the upper part of the Shirataki unit in central Shikoku (Endo et al, ). These similarities suggest that the depositional ages of trench‐fill sediments in close contact with the main mafic schist of the Minawa unit are c .…”
Section: Discussionsupporting
confidence: 84%
“…U-Pb ages of 100-90 Ma for zircons from igneous cobbles in the Koboke unit of the Oboke area in the south of the Ikeda district, central Shikoku, were reported by Aoki, Iizuka, Hirata, Maruyama,and Terabayashi (2007) and Manabe, Yoshikura, & Gabites (1996, April), and these ages were used to show that the protolith of the Koboke unit is younger than 90 Ma. U-Pb ages of 90-80 Ma for detrital zircons from pelitic schists of the Minawa unit in the Oboke area, central Shikoku, were reported by Otoh et al (2010), and U-Pb ages of 95-90 Ma were also reported for detrital zircons from pelitic schists in the Shirataki unit (equivalent to the Minawa unit) of the Asemigawa area, central Shikoku (Endo, Miyazaki, Danhara, Iwano, & Hirata, 2018). Wallis (1990Wallis ( , 1998, where S s is schistosity developed at D s stage.…”
Section: Geological Settingmentioning
confidence: 94%
See 1 more Smart Citation
“…Age of the eclogite facies metamorphism in the Asemi‐gawa region has not been directly determined. However, the youngest age cluster of detrital zircon from psammitic schist in the albite–biotite zone shows 90.3 ±2.2 Ma (Endo et al, ), and the sample locality is within the eclogite unit proposed by Taguchi et al (). More recently, Kinittel et al (2019) reported that detrital zircon has an age of 84 ±4 Ma for a pelitic schist within the Asemi‐gawa eclogite unit; further, they supported the geochronological interpretations of Wallis et al () suggesting eclogite facies metamorphism at ca 89 Ma.…”
Section: Discussionmentioning
confidence: 94%
“…One critical difference in the two models is the depositional age at the trench; the former model considers different deposition and accretion timings between the coarse‐ and fine‐grained lithologies, however, the latter model considers Early Cretaceous or older depositional ages. Recent detrital zircon geochronology revealed that pelitic–psammitic schists in the high‐grade parts of the Besshi and Asemi‐gawa regions contain Late Cretaceous detrital zircon grains ( ca 100–90 Ma) (Aoki et al, ; Endo, Miyazaki, Danhara, Iwano, & Hirata, ; Knittel, Walia, Suzuki, & Lee, ), supporting the Late Cretaceous subduction–exhumation cycle of the high‐grade parts of the Sanbagawa belt (both the eclogite and Shirataki units) except for the coarse‐grained eclogitic bodies.…”
Section: Geological Outlinementioning
confidence: 91%